What makes biology unique? considerations on the autonomy of a scientific discipline - Mayr, Ernst 1904-2005 (Cambridge University Press, 2004)
This book, a collection of essays written by the most eminent evolutionary biologist of the twentieth century, explores biology as an autonomous science, offers insights on the history of evolutionary thought, critiques the contributions of philosophy to the science of biology, and comments on several of the major ongoing issues in evolutionary theory. Notably, Mayr explains that Darwin's theory of evolution is actually five separate theories, each with its own history, trajectory and impact. Natural selection is a separate idea from common descent, and from geographic speciation, and so on. A number of the perennial Darwinian controversies may well have been caused by the confounding of the five separate theories into a single composite. Those interested in evolutionary theory, or the philosophy and history of science will find useful ideas in this book, which should appeal to virtually anyone with a broad curiosity about biology.